If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -10x = 46 + -24X Solving 6 + -10x = 46 + -24X Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -10x = 46 + -6 + -24X Combine like terms: 6 + -6 = 0 0 + -10x = 46 + -6 + -24X -10x = 46 + -6 + -24X Combine like terms: 46 + -6 = 40 -10x = 40 + -24X Divide each side by '-10'. x = -4 + 2.4X Simplifying x = -4 + 2.4X
| 5x^2+26x+24= | | 4n-5=27 | | -3x-4=x+24 | | 5a-40=a | | 10x-118=4x-10 | | -2(3x)= | | 3x+19=2x | | x-9=4x+3 | | x-9=-6 | | 4y=9y-20 | | x+-12=4 | | (-3g)-3=5+g | | 12x+9=6x+11 | | 32x=-64 | | 6v(2v+3)= | | 11n+5=6n | | 127-4=4x+4 | | x=-2p+2px | | 5x+10=73-2 | | 7x=8+5x | | .25q+3=13.75 | | 10-5z=4z-26 | | 7x=8+5 | | 9x-21+8x+34=47 | | -6(x+1)=72 | | 11x-10=9x+1 | | 2(3b+5)=58 | | -3x+4=40 | | (1x-3)(6x-2)= | | 2x-6=-28 | | 0=x^2+20x | | -6X+Y=0 |